Determination of total aflatoxins in cereals by ELISA technique - Bašić, Jasmina; Amidžić, Bisa; Rajić, Jelena; Luković, Bojana; Krsmanović, Slavica; Milanović, Isidora; Dragaš Milovanović, Dragana; Pecarski, Danijela (Archives of Pharmacy, 2022)
Mycotoxins are extracellular metabolites of molds toxic to humans and animals. Mycotoxins can cause acute or chronic adverse effects. Today, various analytical techniques are used for mycotoxin determination. ELISA (Enzyme-Linked Immunosorbent Assay) techniques are most commonly used, but more accurate methods for mycotoxins determination involve liquid or gas chromatography. Determination of total aflatoxins was performed by ELISA technique in cereals, wheat and corn. Aflatoxins were extracted with methanol solution. The extracted aflatoxins were added to the conjugate and the mixture was transferred to antibody-coated wells. After unbound aflatoxins removal, substrate is added, which induces blue color development (color intensity is proportional to conjugated aflatoxins concentration, and inversely proportional to aflatoxins sample concentration). After adding "stop solution", the resulting color intensity is measured on an ELISA reader at 450 nm. Out of 19 wheat samples, 14 samples showed ND (not detected) value below 3 µg/kg, and five samples showed a value from 3 µg/kg to 4.55 µg/kg. Of the 16 maize samples, 10 samples showed an ND value below 3 µg/kg, and two samples a value slightly greater than 3 µg/kg and two samples a value slightly greater than 8 µg/kg. In only one sample, the MDK value was exceeded and amounted to 41.22 µg/kg. MDK of total aflatoxins for wheat is up to 4 µg/kg, MDK of total aflatoxins for corn is up to 10 µg/kg. Results obtained on ELISA reader was checked by comparative analysis using certified material, Fapas QC Material Data Sheet TCL0405QC, CL0405, matrix: Maiye Flour.